IMPLEMENTASI PEMENUHAN HAK NARAPIDANA PEREMPUAN DI LEMBAGA PEMASYARAKATAN (Studi Penelitian Di Lapas Perempuan Kelas II A Medan) - Hakim, Fhaorozhe Rezky; Johari, Johari; Saputra, Ferdy (Fakultas Hukum Universitas Malikussaleh, 2024)
ABSTRACKThe rights of female prisoners are inherently linked to their reproductive functions, ensuring they are guaranteed and protected by law. Therefore, the fulfillment of rights for female prisoners at the Class IIA Women's Penitentiary in Medan is crucial to study and research. The objective of this research is to understand the perspectives and efforts in combating crimes committed by female prisoners, as well as to identify the challenges faced by the penitentiary in handling female inmates.This research method employs qualitative research with an empirical juridical approach. Qualitative methods seek deep understanding of phenomena or events by collecting empirical data through interviews, observations, and analysis. The descriptive nature of this method aims to depict or provide a comprehensive picture of the researched object based on collected data or samples, without generalized analysis or conclusions.The research findings indicate that the fulfillment of rights for female prisoners at the Class IIA Women's Penitentiary in Medan still has several shortcomings that need to be addressed by the penitentiary, including improvements in facilities and competent healthcare partners.Keywords: Fulfillment, The Rights, Prisoners, Female